Ontologies and rules for access control: a feature oriented survey - Gicquel, Pierre-Yves (2023)
Access-control systems are key components to guarantee the security and confidentiality of resource repositories. Most access-control systems that are today de facto standards were designed before the generalization of cloud services and Internet of Things. Such systems are particularly heavy to maintain in today’s context, which gave rise to more flexible approaches based on logical description using semantic web technologies. In this paper, we propose a survey of these semantic approaches. Although this survey does not aim at being exhaustive, it offers the reader an overview of the main trends and their limitations.